2014
DOI: 10.1186/1472-6963-14-s1-s9
|View full text |Cite
|
Sign up to set email alerts
|

Medical and economic benefits of telehealth in low- and middle-income countries: results of a study in four district hospitals in Mali

Abstract: BackgroundThe aim of this study was to evaluate the impact of telehealth on 1) the diagnosis, and management in obstetrics and cardiology, 2) health care costs from patients’ perspectives, 3) attendance at health centres located in remote areas of Mali.MethodsThe impact of telehealth on health care utilization, quality, and costs was assessed using a five-point Likert-scale based questionnaire consisting of three dimensions. It was completed by health care professionals in four district hospitals. The role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 4 publications
(6 reference statements)
2
43
0
Order By: Relevance
“…While IVeH has defined sustainability as the ability of the country to adopt and make telemedicine part of the budget of the MOH; what will happen in the next few years is a matter that will need to be carefully monitored. While the economic effect of telemedicine has been previously addressed [17][18][19] in many public healthcare systems, finding a way to compensate consulting doctors and other medical personnel for their time spent answering telemedicine referrals has been a difficult issue and has not been reported adequately in the literature. 20 Perhaps, this may be one of the reasons why other studies have demonstrated a resistance of adopting telemedicine even when there is clear need for it.…”
Section: Discussionmentioning
confidence: 99%
“…While IVeH has defined sustainability as the ability of the country to adopt and make telemedicine part of the budget of the MOH; what will happen in the next few years is a matter that will need to be carefully monitored. While the economic effect of telemedicine has been previously addressed [17][18][19] in many public healthcare systems, finding a way to compensate consulting doctors and other medical personnel for their time spent answering telemedicine referrals has been a difficult issue and has not been reported adequately in the literature. 20 Perhaps, this may be one of the reasons why other studies have demonstrated a resistance of adopting telemedicine even when there is clear need for it.…”
Section: Discussionmentioning
confidence: 99%
“…However, there remains limited evidence of the cost-effectiveness and the acceptability by both patients and health-care providers of using this technology, and most research to date has been conducted within higher income countries. Recent studies have begun to show promise in addressing the disparity of medical specialists in LMICs by expanding access to sub-specialty training through telehealth (8, 9). Several organizations link multiple groups across geographical and cultural boundaries to provide educational videoconferencing, including the Reseau en Afrique Francophone pour la Telemedicine (10–12), the KwaZulu-Natal Experience (13), and the Global Educational Toxicology Uniting Project (14).…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13] However, there is little evidence demonstrating that these tools lead to changes in health behaviours, which have a meaningful impact on the patient outcomes. An evaluation of a mobile tool for health workers in India used an approach that is similar to the proposed proxy indicators, measuring the impact of the mobile tools on key health behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…They do so by overcoming geographical barriers, increasing access to healthcare services, providing continuing education and enabling collaborative healthcare in remote locations. [3][4][5][6][7][8][9][10][11][12][13] The WHO strengths and limitations of this study ► Limitation: some potential proxy indicators may not have been identified in the systematic review for two possible reasons: (1) due to, for example, a very low GRADE quality, as for some interventions based on ethical reasons, it is not possible to conduct high-quality randomised studies, or (2) no studies have investigated these as they are standard of care. They may also have been overlooked as unforeseen, for example, disruptive uses of eHealth may emerge and offer unexpected ways to improve practices.…”
Section: Introductionmentioning
confidence: 99%